Pyrexia of unknown origin in association with bladder diverticulum tumour. Issue 811 (May 1993) - Agarwal, M.; Azzopardi, A.; Mufti, G. R.
Abstract : A case of pyrexia due to a rapidly growing undifferentiated transitional cell carcinoma in a bladder diverticulum is described. The literature is reviewed and the causes of pyrexia associated with neoplasia briefly discussed.